Godność małżeństwa i rodziny w przesłaniu Konstytucji Gaudium et spes Soboru Watykańskiego II - Rychlicki, Czesław (Ius Matrimoniale, 2015)
The themes and central ideas of Gaudium et Spes of the II Vatican Council are strongly influenced by the Church’s care for dignity of marriage and family. This is exactly the issue that has been the focal point of this study. After indicating the source of marital and family dignity in the Book of Genesis and the St. Paul’s Epistle to the Ephesians, showing the marriage as a covenant of God with his people and Christ with the Church, the Council underlined the holy nature of the marriage and family, resulting from the fact of “recreating” in marriage of the all-encompassing love of Christ to its Church. Talking about such profound dignity of these institutions, the Council does not ignore threats stemming from the modern socio-cultural changes and expresses its concern for regaining this dignity for the good of mankind. The formation of the person is the necessary element to fully understand the dignity of marriage and family. The road to achieve it leads through law, proper education in the family home and at school as well as the humanizing culture of social media and proper cooperation of church institutions with the communities.